Artificial intelligence and its applications in public education: reality and challenges (Journal of Academic Research, 2024)
This research aims to identify the reality of artificial intelligence and the challenges facing its use in the educational process from the point of view of basic education teachers in the city of Misrata. To achieve this goal, the descriptive analytical approach was used, and a questionnaire was prepared by the two researchers that includes two axes: the first dealt with the reality of artificial intelligence in the educational process, and the second: the challenges facing the use of artificial intelligence in the educational process.The research community was represented by all computer teachers in basic education schools in the city of Misrata, with (168) schools, numbering (604) male and female teachers, and the research sample was chosen as a simple random sample of (20%) from the research community approximately, and represents (120) A male and female teacher. It was concluded that the reality of artificial intelligence in education in basic education schools in the city of Misurata was at an average .(67.3%) level with a relative weight of